Expanding telmisartan's therapeutic horizon: exploring its multifaceted mechanisms beyond cardiovascular disorders - Yogesh S. Ahire; Vinod A. Bairagi; Deepak B. Somavanshi; Smruti R. Jadhav; Swapnil B. Jadhav; Shekhar D. Jagtap (SpringerOpen, 2024)
Abstract Background Telmisartan, a potent angiotensin II type-1 receptor blocker as well as partial PPAR-gamma agonist, has emerged as a versatile therapeutic agent with diverse pharmacological actions beyond its primary indication for essential hypertension. This review explores the complex mechanisms of action of telmisartan and clarifies its effectiveness in an inflammation, cancer, metabolic, and CNS disorders. Main body Telmisartan inhibits many biochemical processes involved in the control of the cardiovascular system, such as vascular smooth muscle contraction, aldosterone production, and sympathetic tone modulation, by specifically targeting the angiotensin II type-1 receptor. Its distinct partial agonist action toward peroxisome proliferator-activated receptor gamma also imparts anti-inflammatory, antiproliferative, and antioxidant activities, making it a viable treatment for various diabetic patients who have atherosclerosis and myocardial infarction. Conclusion Telmisartan's diverse pharmacological actions, encompassing anti-inflammatory, neuroprotective, nephroprotective, anticancer, and anti-anxiety properties, position it as a promising treatment option for a broad spectrum of medical conditions.